Pesan Dakwah Dalam Lagu Ebiet G. Ade yang Berjudul untuk Kita Renungkan (Analisis Wacana Kritis Van Dijk) - Urwatul Wusqo (Al-MUNZIR, 2022)
Along with the development of the times, da'wah activities have experienced significant developments, especially in the media sector, namely that they are no longer only carried out on the pulpit but can be through music. The existence of music that is close to the community makes music an effective alternative medium of propaganda. Based on this, this study wants to see the da'wah messages contained in Ebiet G. Ade's song entitled For Us to Reflect. The type of research used is qualitative by using the literature review method. Van Dijk's critical discourse analysis as an approach in this study is to examine the meaning of a language with the process of meaning production and reproduction. The da'wah message contained in Ebiet G. Ade's song entitled "For Us to Think About" is a message about morals, namely remembering and inviting people to improve themselves and repent because all the bad things caused by human behavior will have a bad impact on both the man himself and himself. environment. Apart from containing messages of preaching in the form of morals, it is also in the form of the belief that humans live on earth because of Allah and how humans believe and accept the destiny that Allah wants and humans as servants of Allah so that they always return to Him.Keywords: Da'wah, Music, Van Dijk's critical discourse